(untitled) (Integral Research, 2025)
Folk songs are those spontaneous and natural songs which are sung on the occasion of culture, rituals, festivals, seasons, and social activities of folk life. They are not composed and sung by any specially trained person but by the general public. The tradition of folk songs is Shruti based, that is, they are transferred orally from generation to generation. Folk songs have been divided into various categories, such as ritual songs, agricultural songs, seasonal songs, heroic songs, wedding songs, etc. Many scholars have given definitions regarding folk songs. Dr. Vasudev Sharan Agarwal has described them as the "speaking picture" of a culture, while Pt. Ramnaresh Tripathi has called them "expressions of nature". Through these songs, the emotions, customs and traditions of rural life can be understood. Folk songs vary according to regional and ethnic diversities. Different regions have their own distinctive folk songs, such as Baul Geet in Bengal, Pandavani in Chhattisgarh, Ragini Geet in Haryana, and Abhang Geet in Maharashtra. Kajri, which is mainly popular in eastern Uttar Pradesh, is the main folk song sung during the rainy season in which the separated heroine whines to her lover.